Studies on the Anti-Inflammatory Properties of the Aqueous Ethanol Extract of the Stem Bark of Bombax Costatum P.V - Antwi-Adjei, Meshack (2017)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of the Degree of Master of Philosophy,